2022
DOI: 10.4018/978-1-7998-7492-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Indigenous Knowledge Systems (IKS) in Climate Change

Abstract: Climate change is projected to have a negative effect towards food security and attainment of sustainable development goals (SDGs) in Africa. Its impact is expected to be extremely severe in regions of Africa that depend on rainwater agriculture and have limited resources to mitigate and adapt to climate change. Much of the climate awareness on climate change comes from models or scenarios that face certain degrees of uncertainty. The knowledge of local and indigenous peoples, commonly mentioned to as local kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This is consistent with previous research, which has shown that many science teachers may not recognize IKS' relevance to science education (Lawrence & Maphalala, 2021;Zidny et al, 2020). However, there is a growing body of literature that highlights the importance of incorporating IKS into science education (Kovach, 2021;Kugara et al, 2022). Incorporating IKS into science education can provide a more holistic perspective on science and its role in society.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with previous research, which has shown that many science teachers may not recognize IKS' relevance to science education (Lawrence & Maphalala, 2021;Zidny et al, 2020). However, there is a growing body of literature that highlights the importance of incorporating IKS into science education (Kovach, 2021;Kugara et al, 2022). Incorporating IKS into science education can provide a more holistic perspective on science and its role in society.…”
Section: Discussionsupporting
confidence: 88%
“…The acknowledgment of these difficulties confirms Ogunniyi's finding (2007, p. 964) and highlights a worldwide pattern rather than being specific to South Africa. Similar efforts to integrate IKS into science curricula have been observed in numerous other contexts, including various African countries, Canada, the USA, Australia, the Middle East, Far East, as well as Central and South American countries (de F Afonso Nhalevilo, 2013;Jima, 2022;Kugara et al, 2022).…”
Section: Science Curricula and Indigenous Knowledge Systemsmentioning
confidence: 58%
See 1 more Smart Citation
“…IKS remains an essential source of information amongst local communities in many parts of West Africa. Rural communities value their IKSs as they appreciate that adaptation and mitigation strategies rely on this existing knowledge Stewart Lee Kugara et al, 2022. Indigenous knowledge systems are different from scientific knowledge, which is the system of knowledge that relies on specific laws established through applying the scientific method to phenomena in the world around us. The scientific process begins with an observation followed by a prediction or hypothesis, which is then tested.…”
Section: Introductionmentioning
confidence: 99%
“…When these birds are seen moving in places where people live, it is a sign that rainfall is not yet ready and when they are seen moving out of communities, it indicates that the rainy season is ready, so this helps people to prepare for the farming season.In some African countries such as Malawi though not part of West African subregion, the appearance of the Qualia birds means rains are at hand, and farmers need to prepare their lands (Jiri, Mafongoya, Mubaya, & Mafongoya, 2016). In Tanzania also, local people use the libido of donkeys to forecast climate change; if donkeys' libido increases, this indicates pending drought, and this allows farmers to plant for better options such as the use of rainwater harvesting techniques to store surface runoff and increase soil moisture (Kugara et al, 2022). This will help farmers to overcome drought and improve yields.…”
Section: Introductionmentioning
confidence: 99%